Electroacupuncture efficacy in diabetic polyneuropathy: Study protocol for a double-blinded randomized controlled multicenter clinical trial - María Fernanda Pérez Hernández; Alejandra Calderón Vallejo; Sergio de Jesús Aguilar Castillo; Daniel Cuauhtémoc Gómez Jiménez; Eduardo Rodríguez Guerrero; Fátima Aguilar Morales; Macedonia Guadalupe Moreno Tovar; Miguel Alfredo Zurita Muñóz; Antonio Eduardo Bautista Cortéz; Claudia Camelia Calzada Mendoza; Mónica Ascención De Nova Ocampo; Juan Manuel Ordóñez Rodríguez; et al. (BMC, 2024)
Abstract Background Diabetic peripheral neuropathy (DPN) is the most common complication of type 2 diabetes mellitus (T2DM); its diagnosis and treatment are based on symptomatic improvement. However, as pharmacological therapy causes multiple adverse effects, the implementation of acupunctural techniques, such as electroacupuncture (EA) has been suggested as an alternative treatment. Nonetheless, there is a lack of scientific evidence, and its mechanisms are still unclear. We present the design and methodology of a new clinical randomized trial, that investigates the effectiveness of EA for the treatment of DPN. Methods This study is a four-armed, randomized, controlled, multicenter clinical trial (20-week intervention period, plus 12 weeks of follow-up after concluding intervention). A total of 48 T2DM patients with clinical signs and symptoms of DPN; and electrophysiological signs in the Nerve Conduction Study (NCS); will be treated by acupuncture specialists in outpatient units in Mexico City. Patients will be randomized in a 1:1 ratio to one of the following four groups: (a) short fibre DPN with EA, (b) short fibre DPN with sham EA, (c) axonal DPN with EA and (d) axonal DPN with sham EA treatment. The intervention will consist of 32 sessions, 20 min each, per patient over two cycles of intervention of 8 weeks each and a mid-term rest period of 4 weeks. The primary outcome will be NCS parameters, and secondary outcomes will include DPN-related symptoms and pain by Michigan Neuropathy Screening Instrument (MNSI), Michigan Diabetic Neuropathy Score (MDNS), Dolour Neuropatique Score (DN-4), Semmes-Westein monofilament, Numerical Rating Scale (NRS) for pain assessment, and the 36-item Short Form Health Survey (SF-36). To measure quality of life and improve oxidative stress, the inflammatory response; and genetic expression; will be analysed at the beginning and at the end of treatment. Discussion This study will be conducted to compare the efficacy of EA versus sham EA combined with conventional diabetic and neuropathic treatments if needed. EA may improve NCS, neuropathic pain and symptoms, oxidative stress, inflammatory response, and genetic expression, and it could be considered a potential coadjutant treatment for the management of DPN with a possible remyelinating effect. Trial registration ClinicalTrials.gov. NCT05521737 Registered on 30 August 2022. International Clinical Trials Registry Platform (ICTRP) ISRCTN97391213 Registered on 26 September 2022 [2b].